Inmates’ empathy: relationship with childhood victimization - Almeida, Telma C. (2019)
Poster presented at the 4th International Congress of CiiEM – “Health, Well-being and Ageing in the XXI Century.” 2-5 June 2019, Campus Egas Moniz, Monte de Caparica, Portugal